2 - Recontextualisation of the Concept of Godfatherism: Reflections on Nigeria - Onwuzuruigbo, Ifeanyi (Africa Development, 2021)
Social exchange relations have economic, religious, moral and political implications for both dyadic and group relations. Consequently, some social scientists deploy social exchange theory to explain human actions, behaviour and institutions. The concept of godfatherism, as a form of exchange and clientelist relation, has characterized social, political, religious and commercial networks of indigenous Nigerian groups since pre-colonial times. Recent commentaries and analysis of godfatherism, however, erroneously portray the phenomenon as a new form of political interaction, encouraging electoral fraud, promoting intra-party and political conflicts, and consequently stifling the consolidation of Nigeria’s extant democracy. This superficial treatment of godfatherism, which presents it in a negative image, has proceeded without emphasizing the socio-cultural origin of the concept and its contribution to the political and commercial growth of pre- colonial societies. The paper re-contextualizes the concept of godfatherism. It captures the positive contributions of godfatherism in entrenching responsive and responsible leadership and promoting development. It also considers the distortions the concept suffered as it evolved from a form of social exchange to a form of political relationship, encouraging political conflicts and corruption in colonial and post-colonial Nigeria.